The African Diaspora and the Study of Religion
XIX, 268 p.
Keywords: This book focuses on the location of the religious heritage of Africa within the academic study of religion - including indigenous African religions, African Christianities, African/American forms of Islam, the religions of African Americans, Afro-Caribbean religions, and Afro-Brazilian religions.